Case Report: Four cases of cardiac sarcoidosis in patients with inherited cardiomyopathy—a phenotypic overlap, co-existence of two rare cardiomyopathies or a second-hit disease - Ebbinghaus, Hans; Ueberham, Laura; Husser-Bollmann, Daniela; Bollmann, Andreas; Paetsch, Ingo; Jahnke, Cosima; Laufs, Ulrich; Dinov, Borislav (Frontiers in Cardiovascular Medicine, 2023)
Cardiac sarcoidosis (CS), a rare condition characterized by non-caseating granulomas, can manifest with atrioventricular block, ventricular tachycardia (VT), and mimic inherited cardiomyopathies Summary: A 48-year-old male presented with recurrent VT. Initial 18 F-fluorodeoxyglucose positron emission tomography ( 18 FDG-PET) showed mediastinal lymph node uptake. Cardiovascular magnetic resonance (CMR) demonstrated intramyocardial fibrosis. Follow-up 18 FDG-PET showed tracer uptake in the LV-Septum, suggesting CS. Genetic testing identified a pathogenic LMNA variant. A 47-year-old female presented with palpitations and syncope. An Ajmaline provocation test confirmed Brugada Syndrome (BrS). CMR revealed signs of cardiac inflammation. An endomyocardial biopsy (EMB) confirmed cardiac sarcoidosis. During an electrophysiological study polymorphic VT was induced, and an ICD was implanted. A 58-year-old woman presented with sustained VT and a previous diagnosis of HCM. Genetic work-up identified a heterozygous MYBC3 variant of unknown significance (VUS). CMR revealed LGE, while 18 FDG-PET demonstrated LV tracer uptake. Immunosuppressive was therapy adjusted, no further VTs were observed. A 28-year-old male athlete with right ventricular dilatation and syncope experienced a cardiac arrest during training. Genetic testing identified a pathogenic mutation in PKP2. Autopsy confirmed ACM and distinctive extracardiac sarcoidosis.Cardiac sarcoidosis and inherited cardiomyopathies may interact in several different ways altering the clinical presentation. Overlapping pathologies are frequently overlooked. Delayed or incomplete diagnosis risks inadequate treatment. Thus, genetic testing and endomyocardial biopsies should be recommended to clarify diagnosis.